2009
DOI: 10.1093/annonc/mdp287
|View full text |Cite
|
Sign up to set email alerts
|

Clinician versus nurse symptom reporting using the National Cancer Institute—Common Terminology Criteria for Adverse Events during chemotherapy: results of a comparison based on patient's self-reported questionnaire

Abstract: Our results support the validity of nurse toxicity reporting and that the nurse staff could be successfully employed in collecting toxicity data because of a greater ability to elicit information from patients than the medical staff.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
80
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(87 citation statements)
references
References 18 publications
5
80
0
2
Order By: Relevance
“…Several other authors have reported a similar phenomenon [5][6][7][8][9][10][11] . For example, Di Maio and colleagues recently studied patients enrolled in three prospective clinical trials: one studying elderly patients with breast cancer receiving adjuvant chemotherapy and two studying patients with advanced non-small cell lung carcinoma receiving first-line treatment 9 .…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Several other authors have reported a similar phenomenon [5][6][7][8][9][10][11] . For example, Di Maio and colleagues recently studied patients enrolled in three prospective clinical trials: one studying elderly patients with breast cancer receiving adjuvant chemotherapy and two studying patients with advanced non-small cell lung carcinoma receiving first-line treatment 9 .…”
Section: Discussionsupporting
confidence: 59%
“…Furthermore, the patient experience may not be fully captured by the physicians or nurses documenting clinical findings. Several papers from clinical trials have highlighted discrepancies in the side effects reported by medical staff and patients, with doctors frequently underestimating the incidence and severity of side effects [5][6][7][8][9][10][11] . Since underreporting of chemotherapy-related side effects is a problem even in the highly controlled clinical trial environment, it is likely to be even more pronounced in routine clinical practice, where reporting does not follow strict standards.…”
Section: Introductionmentioning
confidence: 99%
“…However, agreement was low for subjective symptoms such as fatigue and dyspnoea. In a similar study performed in Italy among outpatients undergoing chemotherapy [20], agreement between patients and nurses was generally stronger than those between patients and physicians. Based on these results, the authors suggested that the nurses could be successfully employed in collecting treatment toxicity, because they showed a better performance than doctors in reporting information from the patients.…”
Section: Agreement Between Patients and Physiciansmentioning
confidence: 80%
“…Published studies have consistently demonstrated that health professionals underestimate the incidence and severity of symptoms, when compared with the report by patients [14][15][16][17]. More specifically, a number of publications have been focused on the comparison between patients' and physicians' reporting of treatment adverse events experienced by cancer patients, allowing the description of under-reporting by physicians [18][19][20][21].…”
Section: Agreement Between Patients and Physiciansmentioning
confidence: 99%
“…[17][18][19][20][21][22] Symptom research has looked at patient-clinician agreement of symptoms related to angina pectoris, 23 myocardial infarction, 24,25 psychological and somatic disorders, 8,[26][27][28][29] HIV infection, 30 and cancer. 31,32 One study found fair to substantial agreement between adult selfassessment and clinician assessment on the symptoms related to 'strep throat'. 33 However, there is a relative paucity of primary care reports for infectious diseases, particularly for respiratory infection.…”
Section: Introductionmentioning
confidence: 99%